The Snowline and 0°C Isotherm Altitudes During Precipitation Events in the Dry Subtropical Chilean Andes as Seen by Citizen Science, Surface Stations, and ERA5 Reanalysis Data - Schauwecker, Simone; Palma, Gabriel; MacDonell, Shelley; Ayala, Álvaro; Viale, Maximiliano (Frontiers in Earth Science, 2022)
Understanding the variability of the snowline and the closely related 0°C isotherm during infrequent precipitation events in the dry Andes in Chile is fundamental for precipitation, snow cover and discharge predictions. It is for instance known that on the windward side of mountains, the 0°C isotherm can be several hundreds of meters lower than on the free air upwind counterpart, but little is understood about such effects in the Andes due to missing in situ evidence on the precipitation phase. To bridge this gap, 111 photographs of the snowline after precipitation events between 2011 and 2021 were gathered in the frame of a citizen science project to estimate the snowline altitude. Photographs of the mountain snowline are in good agreement with Sentinel-2 imagery and have a great potential to validate empirical snowline estimations. Using the snowline altitude from the photos, we evaluated different methods to estimate the snowline and 0°C isotherm altitude during precipitation events based on surface meteorological observations and ERA5 reanalysis data. We found a high correlation between the observed snowline altitude and the extrapolated 0°C isotherm based on constant lapse rates (-5.5 to -6.5°C km-1) applied to air temperature from single, near stations. However, uncertainty increases for distances >10 km. The results also indicate that the linear regression method is a good option to estimate ZSL, but the results strongly depend on the availability of high-elevation station datasets. During half of the precipitation events, the 0⁰C isotherm lies between ~1800 and ~2400-2500 m asl. in winter and the snowline is on average ~280 m below this altitude. Our results indicate the presence of a mesoscale lowering of the 0⁰C isotherm over the windward slopes compared to the free-air upwind value during precipitation events, and a possible isothermal layer of near-freezing air temperatures comparable to other mountain ranges. Due to this mesoscale and local behavior, ERA5 data generally overestimate the snow-rain transition in high-elevation areas, especially for relatively intense events. On the other hand, the 0⁰C isotherm altitude is underestimated if only low-elevation valley stations are considered, highlighting the importance of high-altitude meteorological stations in the network.